2002
DOI: 10.1080/02791072.2002.10399960
|View full text |Cite
|
Sign up to set email alerts
|

Hallucinogens and Redemption

Abstract: This article examines drug substitution with regard to hallucinogens (ayahuasca, ibogaine, peyote and LSD) set within the concept of redemption. The model examines both religious and secular approaches to the contemporary use of hallucinogens in drug substitution, both by scientists and in religious settings worldwide. The redemptive model posits that the proper use of one psychoactive substance within a spiritual or clinical context helps to free an individual from the adverse effects of their addiction to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 20 publications
1
24
0
2
Order By: Relevance
“…Notably, every one of the original six studies showed an odds ratio that favored LSD. In addition to these early medical studies suggesting potential efficacy of classic psychedelics in addictions treatment, a number of observational studies documented reports of recovery from addiction to alcohol and other drugs resulting from ceremonies involving classic psychedelic consumption among religions that view such compounds as sacraments [45][46][47][48][49][50][51][52][53][54][55][56]. Consistent with medical and observational studies, the founder of Alcoholic Anonymous, Bill Wilson, was a proponent of the theoretic potential of classic psychedelics to facilitate treatment of addiction.…”
Section: Addictionmentioning
confidence: 99%
“…Notably, every one of the original six studies showed an odds ratio that favored LSD. In addition to these early medical studies suggesting potential efficacy of classic psychedelics in addictions treatment, a number of observational studies documented reports of recovery from addiction to alcohol and other drugs resulting from ceremonies involving classic psychedelic consumption among religions that view such compounds as sacraments [45][46][47][48][49][50][51][52][53][54][55][56]. Consistent with medical and observational studies, the founder of Alcoholic Anonymous, Bill Wilson, was a proponent of the theoretic potential of classic psychedelics to facilitate treatment of addiction.…”
Section: Addictionmentioning
confidence: 99%
“…Our results are in agreement with pre‐clinical studies suggesting that the use of 5‐HT 2A agonists may be useful as therapeutic agents in the treatment of addiction (de Rios et al ., ; Thomas et al ., ; Johnson et al ., ; Loizaga‐Velder & Verres, ). Indeed, the findings are consistent with data showing that administration of 5‐HT 2A receptor agonists is negatively correlated with the development of addictive behavior in human populations (Gable, ).…”
Section: Discussionmentioning
confidence: 99%
“…De même, il est raisonnable de supposer que l'induction du métabolisme énergétique influence l'agilité mentale, l'apprentissage et le recouvrement de la mémoire refoulée [21]. Cela facilite la révélation du statut psychique propre à chacun et augmente l'efficacité de l'approche psychothé-rapique des maladies addictives [9,19].…”
Section: Discussionunclassified
“…Les communautés tribales d'Afrique l'utilisent lors de rites pour des raisons spirituelles depuis des siècles [9]. Localement, on considère que c'est une substance accroissant la perception qui rend l'utilisateur capable d'atteindre les profondeurs du subconscient.…”
Section: Introductionunclassified